Comparative studies on lentic environment of Mai Pokhari, Ilam and Kechana jheel wetland ecosystems, Jhapa, Nepal (With reference to bottom dwelling fauna) - Rai, Kalu Ram Khambu (Nepalese Journal of Biosciences, 2013)
Mai Pokahri is a mountain lake situated in midland at an altitude of 2150 m from sea level whereas Kechana jheel is situated in lowland (Tarai) at an altitude of 63 m from the sea level respectively. The lentic environments of the both lakes vary in the composition of bottomdwelling fauna and limnetic fauna respectively. The comparative studies were carried out in two different years by sampling the macroinvertebrates periodically. The bottom-fauna at Mai pokhari was found higher than Kechana jheel. Mai pokhari is still in natural condition but Kechana jheel is losing its native entity because of aquaculture. Mainly, the abundance of Chironomids showed the stratification in Mai pokhari but abundance of Trichoptera and Coleoptera in Kechana jheel indicate unstable bottom condition because continuous application of manure for pre-conditioning it as a fish pond. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7467 Nepalese Journal of Biosciences 1: 32-36 (2011)